FOTOMETRI DENGAN METODE DIFFERENCE IMAGE - Perhati, Teduh
The study of variable stars can add to our knowledge of their physical parame- ters and evolution. Both of these can be obtained by analyzing the light curve of the variable star. Previously, an appropriate method was needed to detect the variability of star brightness so that the light curve could be obtained. Throughout the history of observations, there have been several methods for obtaining star brightness such as aperture photometry, PSF-tting, and die- rence image. However, the aperture photometry method cannot be applied to crowded star elds and PSF-tting is dicult to apply to images with varying PSF. The proposed method to solve the last problem is dierence image. In its initial version, this method does not take into account background variations and requires a long computational time. The rst dierence image method that succeeded in overcoming these problems was optimal image subtraction (Alard, 2000a). The purpose of this nal project is to study and compare the results obta- ined through this method which is implemented in the ISIS 2.2 program, with other photometric methods. The data used comes from ISIS 2.2 tutorial data and observation data from the Bosscha Observatory. Although this method is the latest method, there are still shortcomings in the data processing process so that it has an impact on the resulting light curve.